Legal Aspects of Creative Economic Development in Digital Economic Development in Padangsidempuan - Mochtar Indra Efendi Siregar; Detania Sukarja; Robert (Journal Equity of Law and Governance, 2024)
Legal aspects of creative economic development in digital economic development by conducting studies in Padangsidempuan City, is important to carry out with the following considerations: There are limitations in terms of legal regulations that both the central government and the regional government of Padangsidempuan City have in supporting the development of the creative economy in digital economic development, so that the implementation of digital economic development in the regions has not run optimally. This research analyzes the legal aspects of developing a digital-based creative economy, the role of local governments in supporting it based on positive laws in Indonesia, as well as the obstacles and the role of the Padangsidempuan City Government in overcoming them. Using a normative juridical method with primary, secondary, literature and field study data, the research concludes that integrated legal support, collaboration between the government and creative economy actors in strategic steps are key to the growth of the digital creative economy in Indonesia, while Padangsidempuan needs to overcome limitations in digital infrastructure, creative education, regulatory harmonization, and intellectual property rights protection. Therefore, it is necessary to develop a strategy for a collaborative model of academia, business and government, or what is called the Triple Helix.